Enhancing Organizational Performance in the Agro-Allied Sector: The Role of Route Planning Management in South-South Nigeria - Bassey Eyo (Mustard Journal De Ecobusin, 2024)
In every economy in the world, but especially in those with abundant agricultural resources, the agro-allied sector is vital.  In addition to creating job opportunities and guaranteeing food security, the industry makes a substantial contribution to the nation's GDP.  This empirical study examines how to improve organizational performance in the agro-allied business through route planning and management.  Although route planning management has been the subject of numerous research, few have looked into the connection between organizational performance and route planning management.  The goal of this study is to close the gap.  By tackling these goals, this research will help shed light on how shipment evaluation management affects organizational performance in the agro-allied sector. Surveys, interviews, and econometric analysis were all used in this mixed-methods study.  The population, which comprises 950 employees from six (6) agro-allied businesses situated in the South-South region of Nigeria, was the sample size of 950 that was used.  Demographic variables were evaluated using means and percentages.  The data was analyzed using multi-regression analysis and the chi-square distribution at the P < 0.001 level of significance to assess the hypothesis's validity.  The findings are presented graphically and in tables.  The study's findings demonstrate that route planning management greatly improves organizational performance, which in turn boosts the South-South Nigerian economy.